Numerical solution for fractionalorder logistic equation - Kaharuddin, Liyana Nadhira (2021)
Recently, in the direction of developing realistic mathematical models, there are a number of works that extended the ordinary differential equation to the fractionalorder equation. Fractional-order models are thought to provide better agreement with